A 'living' necropolis: change and reuse in the cemeteries of Cyrene. (15th October 2018) - Cherstich, Luca; Menozzi, Oliva; Antonelli, Sonia; Cherstich, Igor; Mancini, Maria Cristina; Di Antonio, Maria Giorgia; Sheriff Saad, A. Abdalrahim; Abdel Hati, S. Farag
Abstract: The four cemeteries of Cyrene were a living archaeological landscape whose life continued far beyond antiquity. The habit of using monumental tombs was a long-lasting one in Cyrene, starting in the Archaic period and continuing until Roman times. The concept of 'reuse' is in itself a problematic one since, from a semantic point of view, it implies the presence of a clear-cut division between an original 'phase of use' and of a later 'phase of reuse'. This approach could have sense when a clear hiatus is present, for example when speaking of modern reuse of ancient Greek tombs. However, the main problem is the use of the term 'reuse' when describing two ancient phases, such as a Hellenistic phase and a Roman phase of the same tomb, implying a clear hiatus between them even if one often lacks the elements for identifying the existence of such a hiatus. In particular, the Southern and Northern Necropolises have been analysed here to investigate this subject, basing the hypotheses on data coming from field research and previous studies. However, the topic of reuse for the tombs of Cyrene would need far more space than this paper, so this work should be considered an introduction to a matter that needs a far deeper and a far wider analysis. Given these limits, an 'anthological' approach is here proposed, with a sequence of various subjects connected to the 'reuse' topic and some new data coming from recent research (such as the surveys in the Northern and Southern Necropolises and the excavation of Tomb S1 by the Chieti University team, and of a tomb in the Northern Necropolis by a team of colleagues from the local Department of Antiquities). Abstract : إن المقابر الأربعة في قوريني هي بالفعل مشهد أثري حي استمرت حياته الى ما هو أبعد من العصور القديمة. إن عادة استخدام المقابر ذات النصب التذكارية في قوريني استمرت لفترة طويلة من الزمن، بدءاً من الحقبة العتيقة وحتى العصر الروماني . ويعتبر مفهوم "إعادة الاستخدام " مشكل في حد ذاته، لأنه من ناحية الدلالة اللفظية ينطوي على وجود حد فاصل واضح بين "طور الاستخدام " الأصلي و"طور إعادة الاستخدام " اللاحق . قد يكون لهذه المنهجية معنى عند وجود فجوة واضحة، على سبيل المثال بين إعادة الاستخدام في العصر الحديث للمقابر واستخداماتها في الحقبة الإغريقية القديمة. ولكن المشكلة الرئيسية هي استخدام مصطلح "إعادة الاستخدام " عند وصف حقبتين قديمتين، على سبيل المثال عند وصف طور هلنستي وطور روماني لنفس القبر، مما يشير ضمنياً إلى وجود فجوة واضحة بينهما، وإن كان يفتقد في كثير من الأحيان إلى العناصر اللازمة لتحديد وجود مثل هذه الفجوة. تم هنا تحليل المقبرتين الجنوبية والشمالية على وجه الخصوص لدراسة هذا الموضوع، وبنيت الفرضيات بناءً على البيانات الواردة من الأبحاث الميدانية والدراسات السابقة. ومع ذلك، فإن موضوع إعادة استخدام مقابر قوريني سيحتاج إلى مساحة أكبر بكثير مما هو متاح في هذه المقالة، لذا يجب اعتبار هذا العمل مجرد مقدمة لمسألة تحتاج إلى تحليل أعمق وأشمل بكثير. ونظراً لهذه الحدود، تم اقتراح منهج "أنثولوجكال " (استعمال مجموعات أدبية مختارة)، مع تسلسل من المواضيع المتنوعة المرتبطة بموضوع "إعادة الاستخدام " وبعض البيانات الجديدة من الأبحاث الحديثة (مثل المسح الأثري في المقبرتين الشمالية والجنوبية لفريق جامعة كييتي، وحفريات مقابر S1 من قبل فريق كييتي، وقبر في المقبرة الشمالية من قبل فريق من الزملاء في مصلحة الآثار الليبية).